EFEKTIFITAS KOMPENSASI FINANSIAL DAN PENEMPATAN KERJA DALAM MENINGKATKAN SEMANGAT KERJA KARYAWAN PT. BKS - Risman, Risman (Komunitas Manajemen Kompetitif, 2024)
This research is entitled The Effectiveness of Financial Compensation and Placement in Increasing Work Morale of PT Employees. BKS in Pekanbaru, the aim is to determine the effectiveness of financial compensation and work placement in increasing employee morale. Quantitative analysis includes validity and reliability tests, multiple linear regression tests, F tests and coefficient of determination analysis tests (R2). The research results show that: financial compensation and placement (variables X1, placement is zero, so work morale is 9.917. Meanwhile the value of b1 is 0.383, meaning that when there is an increase in the value of the financial compensation variable (variable X1) by one unit, then work morale (variable Y) will increase by 0.383 units, and b2 is 0.062, meaning that when there is an increase in the value of the placement variable (variable X2) by 1 (one) unit, then work morale (variable Y) will increase by 0.062 units. It is known that calculated F is 3.820 and table F is 3.22. The calculation results show that F count > F table and the significance is 0.037 < 0.05, which means that simultaneously the variables of financial compensation and work placement have an effect on work morale. The coefficient of determination (R Square) value is 0.508 or 50.8%, which means that the financial compensation and work placement variables influence work morale, contributing to changes in the work morale variable of 50.8%. Keywords: Financial Compensation ,Placement and Work Morale.